KERAGAAN POPULASI FAMILI HALFSIB HASIL PERSILANGAN UBIJALAR UNTUK PENGKAYAAN MIKRONUTRIEN - Sri Umi Lestari (Buletin Palawija, 2017)
Hidden Hunger is a major health problem for the world populations, especially in developing countries. Sweet potato is one of the main staple crops to be enriched with micro nutrient content through biofortification program, to overcome the Hidden Hunger. The study aim was evaluated the offspring performance of the controlled crosses between the parent for the enrichment of micro nutrient content with other high yielding clones. A number of hybrid genotypes (297) scattered in 8 families of half sibs were evaluated by weight of storage root and vines, estimated of storage root and vines yields per hectare, and its micronutrient content (Fe and Zn). Augmented Randomized Block Design with 8 replicate blocks was applied for this trial. In each block is also planted parent clones as control cultivars. The results showed that cultivar test performance on all observed parameters was different to control cultivars, as well as among the cultivars test were also statistically different. This allows obtaining the selection of genotype based on storage root weight/plant and its micronutrient content. Among the 297 genotypes evaluated available of 140 genotypes had storage root yields ≥ 0.5 kg/plant and 6 of them had storage root weight of ≥ 1.5 kg/plant. Based on storage root weight and micro nutrient content selected 6 genotypes with the storage root weight range between 0.598 - 1.631 kg/plant and Fe and Zn content respectively ranged from 95 to 618 mg Fe/kg and 10-12 mg Zn/kg based on dry weight basis.